Anti-Inflamatory and analgesic activities of securidaca longepedunculata fers (Polygalaceae) leaf and stem bark methanolic extract (2014)
Securidaca longepedunculata Fers (Polygalaceae) is commonly used in many parts of Africa for the treatment of rheumatic conditions, fever, headache and various other inflammatory based diseases. The present study was carried out to evaluate the anti-inflammatory and analgesic activity of Securidaca longepedunculata leaf and stem bark methanol extracts using animal model. The anti-inflammatory activity of the methanolic extracts were evaluated using carrageenan induced paw edema in rats while the analgesic activity was determined using acetic acid induced writhing in mice. Both the leaf and stem methanol extracts exhibited anti-inflammatory activity greater than 70% at all doses tested. This activity was dose dependent with the highest being at 800 mg/kg Po and significant at P< 0.05. The analgesic activity of both extract was however below 50%, though comparable with that of aspirin used as the standard. This study has justified the inclusion of Securidaca longepedunculata in remedies used for the management of inflammatory based diseases traditionally.